KIF11 promotes rheumatoid arthritis pathogenesis by activating M1 macrophage polarization and promoting inflammatory cytokine secretion - Zhaonan Ban; Yongjie Ye; Hang Zhong; Zhengjiang Li; Zhangzhen Du; Wanquan Cao; Lei Yang; Shuxing Xing (PLoS ONE, 2026)
Background and Objective KIF11, a mitotic kinesin, has been implicated in oncogenesis, but its specific role and mechanism in RA pathogenesis remain largely unexplored. We aim to explore functional role and molecular mechanism of KIF11 to promote RA progression. Methods Bioinformatics analysis was first performed on public RA datasets (GSE55457, GSE55235, GSE2053, GSE12021, and GSE1919) to identify KIF11-associated DEGs and their enriched pathways using GO/KEGG and GSEA analysis. Lentivirus-mediated shRNA was employed to knock down KIF11 expression in MH7A cells and M1-polarized macrophages. The effects on macrophage activation were assessed by FACS for the surface marker CD86. The expression of inflammatory cytokines were measured by quantitative PCR and ELISA, respectively. Results Bioinformatic analysis showd that KIF11-associated genes were significantly enriched in immune activation pathways, especially adaptive immune system and cytokine-cytokine receptor interaction. In vitro data demonstrated that KIF11 knockdown suppressed the M1 macrophage phenotype, with a marked decreased expression of CD86. Furthermore, KIF11 deficiency led to a profound decrease in the mRNA levels and protein secretion of cytokines in M1 macrophages. Conclusion Depletion of KIF11 markedly inhibited the proliferation, migration, and inflammatory cytokine secretion in MH7A and attenuated the maturation of M1 macrophages, as well as the production of inflammatory cytokines, suggesting its pivotal role in RA pathology.